H i 21 cm observation and mass models of the extremely thin galaxy FGC 1440. Issue 3 (1st November 2021) - Aditya, K; Kamphuis, Peter; Banerjee, Arunima; Borisov, Sviatoslav; Mosenkov, Aleksandr; Antipova, Aleksandra; Makarov, Dmitry
ABSTRACT: We present observations and models of the kinematics and distribution of neutral hydrogen (H i ) in the superthin galaxy FGC 1440 with an optical axial ratio a / b  = 20.4. Using the Giant Meterwave Radio telescope (GMRT), we imaged the galaxy with a spectral resolution of 1.7 km s −1 and a spatial resolution of 15${_{.}^{\prime\prime}}$ 9 × 13${_{.}^{\prime\prime}}$ 5. We find that FGC 1440 has an asymptotic rotational velocity of 141.8 km s −1 . The structure of the H i disc in FGC 1440 is that of a typical thin disc warped along the line of sight, but we cannot rule out the presence of a central thick H i disc. We find that the dark matter halo in FGC 1440 could be modelled by a pseudo-isothermal (PIS) profile with $\\ R_{\rm c}/ R_{\rm d} \lt 2$, where R c is the core radius of the PIS halo and R d the exponential stellar disc scale length. We note that in spite of the unusually large axial ratio of FGC 1440, the ratio of the rotational velocity to stellar vertical velocity dispersion, $\frac{V_{\rm Rot}}{\sigma _{z}} \sim 5 - 8$, which is comparable to other superthins. Interestingly, unlike previously studied superthin galaxies which are outliers in the log10 ( j * ) − log10 ( M * ) relation for ordinary bulgeless disc galaxies, FGC 1440 is found to comply with the same. The values of j for the stars, gas, and the baryons in FGC 1440 are consistent with those of normal spiral galaxies with similar mass.